Screening attendance, age group and diabetic retinopathy level at first screen. Issue 7 (6th October 2015) - Scanlon, P. H.; Stratton, I. M.; Leese, G. P.; Bachmann, M. O.; Land, M.; Jones, C.; Ferguson, B; ,
Abstract: Aims: To report on the relationships between age at diagnosis of diabetes, time from registration with the screening programme to first diabetic eye screening and severity of diabetic retinopathy. Methods: Data were extracted from four English screening programmes and from the Scottish, Welsh and Northern Irish programmes. Time from diagnosis of diabetes to first screening and age at diagnosis were calculated. Results: Time from registration with the screening programme to first screening episode is strongly related to age at registration. Within 18 months of registration 89% of 3958 young people under 18 years of age and 81% of 391 293 people over 35 years of age were seen. In 19 058 people between 18 and 34 years of age, 80% coverage was not reached until 2 years and 9 months. The time from diagnosis of diabetes to first screening is positively associated with severity of disease ( P < 0.0001). Conclusions: This report is the first that to demonstrate that those in the 18–34 year age group are least likely to attend promptly for screening after registration with a higher risk of referable diabetic retinopathy being present at the time of first screen. Date of diagnosis should be recorded and prodigious efforts made to screen all people promptly after diagnosis. Screening programmes should collect data on those who have not attended within one year of registration. What's new?: People in the 18–34 year age group are more likely to have a longer time interval between registration with the screening programme and attendance for screening. People with a longer time interval between registration and attendance for screening are at a greater risk of referable diabetic retinopathy being present at the time of first screen.